ANALISIS KUALITAS WEBSITE UNIVERSITAS SATYA NEGARA INDONESIA MENGGUNAKAN MODEL WEBQUAL 4.0 - Sibarani, Riama (JURNAL SATYA INFORMATIKA, 2024)
Satya Negara Indonesia University has utilized its website as a service platform for disseminating information to the academic community. However, no research has yet analyzed the website's quality from the perspective of user satisfaction. This study aims to evaluate the website using the WebQual 4.0 method, focusing on usability, information quality, and interaction quality, and their impact on user satisfaction. The research involves formulating hypotheses, testing instruments, collecting primary data, and performing statistical analyses, including validity, reliability, normality, correlation, and regression tests. Results indicate that usability is the most significant factor influencing user satisfaction. Improvements in information and interaction quality are recommended to enhance overall website quality and user satisfaction further.